Main factors related to cardiovascular risks for Indigenous Populations of Brazil (Research, Society and Development, 2021)
The Brazilian indigenous population has been going through a process of change in the profile of its most prevalent diseases. Thus, infectious and parasitic diseases have lost the podium for chronic non-communicable diseases. Among them, cardiovascular diseases are the ones with the greatest increase in prevalence, which increases the risk of events that could compromise the quality of life and the health of these ethnic groups. Little is known about the cardiovascular risks that the Brazilian indigenous population presents, as few studies target these groups. Therefore, this review aimed to track the main factors reported in the literature. We have observed the urbanization was the triggering factor for the onset of cardiovascular diseases, generating a sedentary lifestyle and changes in eating habits. These factors have been reported as the main causes of the increase in the number of individuals with obesity, hypertension and dyslipidemia. Type 2 Diabetes mellitus is still uncommon in individuals without other comorbidities, but its prevalence increases fivefold when there is an associated disease. Therefore, Brazilian ethnic groups need more educational and health support to prevent and treat chronic non-communicable diseases, and greater concern is needed to monitor the incidence of these conditions within indigenous territories.